ANALISIS PENGELOLAAN ARSIP PADA BPJS KETENAGAKERJAAN CABANG MAGELANG - Purwanti, Deverin Dwi; Wolor, Christian Wiradendi; Marsofiyati, Marsofiyati (LPPM Politeknik Pajajaran ICB Bandung, 2023)
This study used qualitative research methods. The author uses primary data sources and secondary data sources. The primary data sources used in this research are observations, interviews and questionnaires filled out by several respondents. The data collection technique was in the form of interviews with employees regarding the topic being researched and researchers also carried out observations and interviews at the BPJS Ketenagakerjaan Magelang Branch Office. In this research, the resource person is an archivist who directly handles archives from collection to deletion. The main aim of this research is to find out how records management occurs at the BPJS Ketenagakerjaan Magelang Branc Office, including the impact and solutions for the records management carried out. The results of this research show that the Covid 19 pandemic has had a big impact on the management carried out, there are also several impact that have occurred and how the BPJS Ketenagakerjaan Magelang Branch Office can adapt to the changes that have occurred. This finding is strengthened by the results of interviews which show that the transition from conventional archives to digital archives has had a big impact on the work of archive managers and there has been a gradual simplification of the organizational structure at the BPJS Ketenagakerjaan Magelang Branch Office.